MUTASI TITIK HINGGA MUTASI FRAMESHIFT GEN INSR EXON 22 PADA PASIEN PENDERITA DIABETES MELLITUS - Fatchiyah Fatchiyah; S. Widyarti; I. Mustofa; IY. Kusumowardhani; R. Fatimah; L. Firdausi; SP. Ayu; Aulanni’am Aulanni’am; DW. Soeatmaji (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Mutations of human insulin and insulin receptor family can lead autosomal dominant syndrome on diabetes, fasting hyperinsulinemia, and insulin resistant. The aim of this research was to identify mutation types of hINSR gene exon 22 which mutation hot spot region. To analyze hINSR gene exon 22 of DM patient and control, we isolated DNA from their blood. DNA was then amplified by PCR using a set of primer for exon 22. PCR product was sequenced by Sequencer and nucleotide sequence analyzed by BLAST analysis. According to Gene Bank database, hINSR gene has two variant with Gene ID 3643, at chromosome 19p13.3-p13.2, and has 22 exons with mRNA 4200bp. The result of research showed that the mutation types of hINS gene exon 22 of DM patients are point mutation, single base deletion and substitution. We found mutation of single deletion at Met1295 Cys1295 and Glut1300Gly1300, also point mutation are at Met1296 Ser1296 and Trp1299Ala1299 and Met1389 Iso1389. Because these two deletion are so close, the polypeptids sequenceof these changed as frameshift mutation, normal IR has six amino acids Met Arg Met Cys ????Trp ????Glut- and DM patient has differed the five amino acids - Cys Ala Ser Ala Gly. According to the mutation of DM patient, the IR protein function against tyrosine kinase become abnormal, perhaps its were correlated with genetic syndrome of insulin resistance.